2003
DOI: 10.1109/jlt.2003.808769
|View full text |Cite
|
Sign up to set email alerts
|

Low-density parity check codes and iterative decoding for long-haul optical communication systems

Abstract: A forward-error correction)FEC) scheme based on low-density parity check (LDPC) codes and iterative decoding using belief propagation in code graphs is presented in this paper. We show that LDPC codes provide a significant system performance improvement with respect to the state-of-the-art FEC schemes employed in optical communications systems. We present a class of structured codes based on mutually orthogonal Latin rectangles. Such codes have high rates and can lend themselves to very low-complexity encoder/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…(The derivation of the expressions (4) and (5) is given in our previous paper [20].) The autocorrelation function of the optical filter output noise can be expressed as (6) where is the optical filter autocorrelation function. Notice that the photodiode output noise process is not stationary (the mean values and the standard deviation are functions of time).…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…(The derivation of the expressions (4) and (5) is given in our previous paper [20].) The autocorrelation function of the optical filter output noise can be expressed as (6) where is the optical filter autocorrelation function. Notice that the photodiode output noise process is not stationary (the mean values and the standard deviation are functions of time).…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…Ait Sab proposed a concatenated scheme with two Reed-Solomon (RS) codes and another scheme with block turbo codes (BTCs) [3]- [5]. In a series of recent articles, we showed that error performance and decoder hardware complexity offered by turbo codes can be greatly improved by using other types of iteratively decodable coding schemes, in particular low-density parity-check (LDPC) codes [2], [6]. The LDPC codes have been shown to perform approximately within 0.005 dB of the Shannon limit on an additive white Gaussian noise (AWGN) channel (rate 1/2, codeword size of ) [7], breaking the record previously set by turbo codes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At any symbol rate and code rate, H-SAPP is capable of achieving the aggregate rate of the individual HAPP systems it is composed of, without introducing any bit-error-ratio (BER) performance degradation, as long as the orthogonality among subcarriers is preserved. In this letter, coding is done using structured low-density parity-check (LDPC) codes [1]. Structured LDPC codes are chosen for this scheme to allow easier iterative exchange of the extrinsic soft bit reliabilities between the equalizer and the LDPC decoder, and to reduce the encoding complexity in comparison to the random codes, as encoding is done using linear shift register circuitry.…”
mentioning
confidence: 99%